ANTAGONIST’S HATRED TOWARDS PIRATES IN JEFF NATHANSON’S NOVEL PIRATES OF THE CARIBBEAN: SALAZAR’S REVENGE - Haris Al-Rasyid Simanungkalit; M. Amrin Siregar (JOURNAL OF LANGUAGE, 2020)
Hatred has a lot of negative impacts on the hated person and the hating one. The impacts appear due to the existence of the causes and the implementation of the hatred. The purpose of this study is to research the causes and the implementation of the antagonist’s hatred in Jeff Nathanson’s novel Pirates of the Caribbean: Salazar’s Revenge. In this analysis, the antagonist, Captain Slazar, hates pirates very much especially the protagonist, Captain Jack Sparrow. His life’s goal is only to kill Jack in all kinds of ways. This research uses qualitative research method proposed by Gilgun (1992:22) who clarifies a research method that is more focused on understanding social phenomena from the perspective of participants by emphasizing on the complete picture rather than by detailing it into interrelated variables. This study focuses on the analysis or interpretation of written materials based on the context. In this case, the novel has to be well interpreted. Results establish the fact that hatred does not only harm the others, but also oneself. Besides, it will tell how bad the hatred affects oneself. This study also reveals how the antagonist releases the hatred to the protagonist by pursuing and trying to kill him.